Usability meets security: a database case study - Wang, Yong; Rawal, Bharat (Journal of Advanced Computer Science & Technology, 2017)
Abstract In this paper, we review security and usability scenarios. We propose security enhancements without losing usability and apply a new approach to popular application systems. Specifically, we analyze database security for access control, auditing, authentication, encryption, integrity control, backups, separation of environment, and secure configuration. Finally, we present our recommendations for system security and usability that work together.